Excess mortality and associated sociodemographic factors during the COVID-19 pandemic in rural Pune Maharashtra, India: a retrospective data analysis from the Vadu health and demographic surveillance system - Uddhavi Kand; Chodziwadziwa Kabudula; Bharat Choudhari; Tapas Kumar Mohanty; Sandeep Bhujbal; Arunkumar Gondhali; Jean J. H. Bashingwa; Beth A. Tippett Barr; Stephen Tollman; Sanjay Juvekar; Anand Kawade; Dhiraj Agarwal (Population Health Metrics, 2026)
Abstract Background Between January 2020 and August 2023, India documented over 450 million confirmed cases of COVID-19 and nearly 0.5 million COVID-19 deaths. While reported mortality rates in India appeared lower than expected, the actual mortality may be higher due to underreporting and disparities in healthcare access. This study aimed to compare mortality before and during the COVID-19 pandemic and identify associated socio-demographic factors in rural Pune, Maharashtra, India using longitudinal population-based data from the Vadu Health and Demographic Surveillance System. Methods Individual and mortality data from the Vadu HDSS, India were collected from 2018 to 2021. Descriptive analyses were conducted to examine the variation in mortality by sociodemographic factors during pre-COVID-19 [2018–2019] and COVID-19 [2020–2021] periods. Cox regression with hazard ratios [HR] and 95% confidence intervals [CI] were used to measure the association between socio-demographic factors and mortality. Results There were 2039 deaths that occurred between 2018 and 2021, of which 40.6% [828/2039] were female. The overall risk of mortality increased during COVID-19 [HR1.2,95%CI:1.1–1.3], but this varied by sociodemographic characteristics. The risk of death was greater [HR1.8,95%CI:1.5–2.2] among individuals living in single-person households compared to those living in 2–5 member households, and there was a strong trend of increased mortality risk with older age. Widowed individuals had a greater risk of mortality than those who were married [HR2.1,95%CI:1.9–2.4]. Education was strongly protective against mortality; those who had any level of education had a lower risk of dying than those with no education [HR0.4,95%CI:0.3–0.5]. Conclusion Increased COVID-19 mortality in India was associated with older age, widowhood, and living alone. These findings highlight the need for targeted vaccination, early clinical care, and community outreach for vulnerable populations during future pandemics.